TARDBP in amyotrophic lateral sclerosis: identification of a novel variant but absence of copy number variation. - Bäumer, D; Parkinson, N; Talbot, K (2009)
BACKGROUND: Mutations in the gene encoding TDP-43 have been identified in both familial and sporadic amyotrophic lateral sclerosis (ALS). METHODS: A mutation screen and copy number analysis in a motor neuron disease clinic cohort was conducted to characterise the genetic contribution of TARDBP. RESULTS: A novel missense mutation in a highly conserved region of TDP-43 was identified in a patient with sporadic ALS. The mutation is in close vicinity to previously identified changes. Copy number variation abnormalities were not detected. CONCLUSIONS: The findings stress the importance of TDP-43 in the pathogenesis of sporadic ALS.